A Colisão de direitos fundamentais na jurisprudência do Supremo Tribunal Federal - Carvalho, Joana de Moraes Souza Machado (2006)
The fundamental rights arose from the need to limit state action, but is now indisputable the fact that assumed an axiological character, wider, ensuring the dignity of the human person. Much has fought for the recognition of human rights since the Declaration of the Rights of Man and of the Citizen in 1948, but it was found that only the recognition of these rights by statements was insufficient because they had no legal force, making up, then, it necessary to positivation or constitutionalization. The Charter Policy 1824 was the first to make positive these rights, even before the Constitution of Belgium, 1831. The 1988 Constitution brought a title on the Rights and Fundamental Guarantees, under a modern perspective, covering individual and collective rights, social rights, nationality and political rights. The study of the principle of human dignity is essential, it is characterized as a set of fundamental rights. This principle ensures respect for each and every human being, for all are endowed with equal dignity. Fundamental rights are characterized as principles, whereas in the event of a conflict between them, should make the decision not to withdraw the validity of any of them, should prevail only one of them. The principles are optimization warrants, characterized by the fact of being fulfilled in proportion to the factual and legal conditions. When the exercise of a fundamental right by a holder colliding with the exercise of other fundamental rights or when the exercise of a fundamental right hit with the need to preserve a collective good before is up a rights collision hypothesis fundamental. In this case, the interpreter must apply an interpretation of constitutional principles, especially the principles of unity of the Constitution, the practice agreement and normative force of the Constitution. Not being sufficient to apply these principles, it will be duty to employ the method of weighting assets by the principle of proportionality, which is to adopt a preemptive decision between the rights and property in conflict, determining which law should prevail.